Analysis of Trade Openness and Macroeconomic Variables on Foreign Direct Investment in Indonesia for the Period 1980-2022 - Nisa, Khoirun; Khilmi, Slamet (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2023)
This study analyzes trade openness and macroeconomic variables on foreign investment in Indonesia. This study uses Indonesian time series data from 1980 to 2022. The data analysis technique uses the Autoregressive Distributed Lag (ARDL) method. Data were analyzed using data stationarity test, optimal lag test, CUSUM test, classical assumption test, cointegration test and ARDL estimation processed with Eviews 10. The results showed that indirect trade openness has a positive and significant effect on Foreign Direct Investment (FDI) in the short term and long term. The exchange rate (IDR to USD) has a negative and significant effect on Foreign Direct Investment (FDI) in the short and long term. Inflation rate in the short term has a positive and significant effect but in the long term has a negative and insignificant effect on Foreign Direct Investment (FDI). GDP has a negative and significant effect in the short term but in the long term has a significant positive effect on Foreign Direct Investment (FDI).